The trend of changes in air quality index (AQI) in Mashhad using ‎GIS ‎ - mohammad Miri; Amir Mohammadi; Sepideh Nemati; Ali Abdolahnejad; Ali Nikonahad (Mazandaran University of Medical Sciences, 2016)
Introduction and Purpose: Mashhad, one of the most populous cities in Iran, is facing air pollution due to motor vehicle emissions and industries. Therefore, this study aimed to evaluate the variations in Air Quality Index (AQI) during the spring of 2012-2014 and its spatial zoning with Arc GIS. Methods: In this descriptive study, the AQI values were calculated by the associated pollutant concentrations including PM10, PM2.5, NO2, SO2, CO, and O3 obtained from four online stations in the city during the spring of 2012-2014. After classification of daily air quality into six categories (good, moderate, unhealthy for sensitive people, unhealthy, and very unhealthy), the spatial zoning was performed with Arc GIS. Results: Based on the results, the air quality of Mashhad was found to be good and moderate most days for which PM2.5 and NO2 emissions were recognized to be the main responsible pollutants. According to the zoning maps, AQI values were found to be in good conditions in Sadaf station located in the northwest of Mashhad, while the center and south of Mashhad were more polluted during 2012-2014. AQI values improved from April to June 2012-2013, while the values dropped in 2014.Conclusion: The air quality of Mashhad is unhealthy in the crowded southern and center regions of this city on some spring days. Consequently, some strategies, such as traffic management, employment of other types of fuel or quality improvement, management of home heating systems, and use of electric transportation should be considered as air pollution control options in the coming years.